Bardet-Biedl Syndrome in rhesus macaques: A nonhuman primate model of retinitis pigmentosa. (December 2019) - Peterson, Samuel M.; McGill, Trevor J.; Puthussery, Teresa; Stoddard, Jonathan; Renner, Lauren; Lewis, Anne D.; Colgin, Lois M.A.; Gayet, Jacqueline; Wang, Xiaojie; Prongay, Kamm; Cullin, Cassandra; Dozier, Brandy L.; et al.
Abstract: The development of therapies for retinal disorders is hampered by a lack of appropriate animal models. Higher nonhuman primates are the only animals with retinal structure similar to humans, including the presence of a macula and fovea. However, few nonhuman primate models of genetic retinal disease are known. We identified a lineage of rhesus macaques with a frameshift mutation in exon 3 of the BBS7 gene c.160delG (p.Ala54fs) that is predicted to produce a non-functional protein. In humans, mutations in this and other BBS genes cause Bardet-Biedl syndrome, a ciliopathy and a syndromic form of retinitis pigmentosa generally occurring in conjunction with kidney dysfunction, polydactyly, obesity, and/or hypogonadism. Three full- or half-sibling monkeys homozygous for the BBS7 c.160delG variant, at ages 3.5, 4 and 6 years old, displayed a combination of severe photoreceptor degeneration and progressive kidney disease. In vivo retinal imaging revealed features of severe macular degeneration, including absence of photoreceptor layers, degeneration of the retinal pigment epithelium, and retinal vasculature atrophy. Electroretinography in the 3.5-year-old case demonstrated loss of scotopic and photopic a-waves and markedly reduced and delayed b-waves. Histological assessments in the 4- and 6-year-old cases confirmed profound loss of photoreceptors and inner retinal neurons across the posterior retina, with dramatic thinning and disorganization of all cell layers, abundant microglia, absent or displaced RPE cells, and significant gliosis in the subretinal space. Retinal structure, including presence of photoreceptors, was preserved only in the far periphery. Ultrasound imaging of the kidneys revealed deranged architecture, and renal histopathology identified distorted contours with depressed, fibrotic foci and firmly adhered renal capsules; renal failure occurred in the 6-year-old case. Magnetic resonance imaging obtained in one case revealed abnormally low total brain volume and unilateral ventricular enlargement. The one male had abnormally small testes at 4 years of age, but polydactyly and obesity were not observed. Thus, monkeys homozygous for the BBS7 c.160delG variant closely mirrored several key features of the human BBS syndrome. This finding represents the first identification of a naturally-occurring nonhuman primate model of BBS, and more broadly the first such model of retinitis pigmentosa and a ciliopathy with an associated genetic mutation. This important new preclinical model will provide the basis for better understanding of disease progression and for the testing of new therapeutic options, including gene and cell-based therapies, not only for BBS but also for multiple forms of photoreceptor degeneration. Graphical abstract: Image 1 Highlights: A rhesus monkey family was identified with Bardet-Biedl syndrome (BBS). Affected monkeys show key features of BBS including retina and kidney degeneration. The syndrome is linked to a frameshift mutation in BBS7, part of the BBSome. This is the first monkey model of retinitis pigmentosa with known genetic cause. This model will have great value for testing new therapies for blinding diseases.